Cell yield, chondrogenic potential, and regenerated cartilage type of chondrocytes derived from ear, nasoseptal, and costal cartilage. (13th December 2017) - He, Aijuan; Xia, Huitang; Xiao, Kaiyan; Wang, Tingting; Liu, Yu; Xue, Jixin; Li, Dan; Tang, Shengjian; Liu, Fangjun; Wang, Xiaoyun; Zhang, Wenjie; Liu, Wei; et al.
Abstract: Functional reconstruction of large cartilage defects in subcutaneous sites remains clinically challenging because of limited donor cartilage. Tissue engineering is a promising and widely accepted strategy for cartilage regeneration. To date, however, this strategy has not achieved a significant breakthrough in clinical translation owing to a lack of detailed preclinical data on cell yield and functionality of clinically applicable chondrocytes. To address this issue, the current study investigated the initial cell yield, proliferative potential, chondrogenic capacity, and regenerated cartilage type of human chondrocytes derived from auricular, nasoseptal, and costal cartilage using a scaffold‐free cartilage regeneration model (cartilage sheet). Chondrocytes from all sources exhibited high sensitivity to basic fibroblast growth factor within 8 passages. Nasoseptal chondrocytes presented the strongest proliferation rate, whereas auricular chondrocytes obtained the highest total cell amount using comparable cartilage sample weights. Importantly, all chondrocytes at fifth passage showed strong chondrogenic capacity both in vitro and in the subcutaneous environment of nude mice. Although some significant differences in histological structure, cartilage matrix content and cartilage type specific proteins were observed between the in vitro engineered cartilage and original tissue; the in vivo regenerated cartilage showed mature cartilage features with high similarity to their original native tissue, except for minor matrix changes influenced by the in vivo environment. The current study provides detailed preclinical data for choice of chondrocyte source and thus promotes the clinical translation of cartilage regeneration approach.